The GDR today : new interdisciplinary approaches to East German history, memory and culture - Ehrig, Stephan 1986- HerausgeberIn; Thomas, Marcel 1991- HerausgeberIn; Zell, David 1947- HerausgeberIn; Peter Lang Ltd (Studies in modern German and Austrian literature, 2018)
"The GDR Today promotes interdisciplinary approaches to East Germany by gathering articles from a new generation of scholars in the fields of literary and visual studies, history, sociology, translation studies, political science, museum studies and curating practice. The contributors to this volume argue that it is necessary to transgress disciplinary boundaries to escape the gridlocked categories of GDR scholarship. Exploring East German everyday life, cultural policies, memory and memorialisation, the volume aims to offer new impulses to the study of the GDR. Through the combination and juxtaposition of different approaches to East Germany, it overcomes intra-disciplinary conceptual binaries and revitalises debates about the very concepts we use to understand life under late twentieth-century state socialism" .--